Examining the rising class of young Chinese Singaporeans : their aspirations for the cosmopolitan lifestyle - Hu, Amie Heang-Gee (2016)
In this paper, I investigate the challenges that the young Singaporean Chinese overseas community face as they pursue a cosmopolitan lifestyle through the understandings of Beck (2002) and Giddens (2001) works on the consequences of cosmopolitanism. The research will also expound upon the concept of nation as an imagined community (Anderson 1983). I draw upon data collected from semi-structured interviews with 23 young Singaporeans aged between 21 and 29. Findings suggest that consequences of transnational interconnectivity have bearings on how Singaporeans’ sense of national identity can be strengthened and diluted and furthermore, encourage them to develop interactional skills. Altogether, we can observe how the State’s role in evoking national identity is fundamental in these Singaporeans’ formative years, but less so during their stint overseas. Feelings of nationalism stem from their identification with this deterritorialized national community they seek ontological security from.